The role of auditor in whistleblower system: The cases in Indonesia - Nurul Hasanah Uswati Dewi; Djuwito Djuwito; Romanus Wilopo (Universitas Hayam Wuruk Perbanas, 2015)
In 2012, the Association of Certified Fraud Examiners stated that 43% of frauds are detected by tip money. The role of tips for the people is a crucial factor in disclosing frauds. Most often, company frauds are revealed by a whistle blower. This study attempts to observe the dimensions of the existence and role of the organization of internal auditors and the witness protection agency as external factors influencing an internal auditor to become a whistle-blower. It also explores the effects of the internal auditor competencies, the moral attitude of the internal auditor, and the ethical behavior of company’s internal auditors as internal factors influencing an internal auditor on being a whistle-blower. The independent auditors are considered as the population as they are often connected with the internal auditors. They need the information from the internal auditor about fraud or abuse in the company. Questionnaires were mailed to them and analyzed using Partial Least Squares. It showed that only the ethical behavior of company’s internal auditors influenced them to be whistle blowers coupled by a witness protection program. To develop sound corporate governance in Indonesia, a whistle blower system is needed with emphasis on a strong witness protection. At present, Indonesia does not have the whistle blower act.